Response of 45S5 Bioglass® foams to tensile loading - Rehorek, L.; Chlup, Zdenek; Meng, D.; Yunos, D. M.; Boccaccini, Aldo R.; Dlouhy, Ivo (Ceramics International, 2013)
The tensile strength test of highly porous ceramic foams has been developed and first results have been obtained on bioactive glass foams. The tested material was a 45S5 Bioglass® derived foam-like scaffold intended for use in bone tissue engineering which was manufactured by Bioglass® slurry coating of polyurethane foam and subsequent sintering. The Bioglass® foam structure was investigated in two states: uncoated (as fabricated) and with a PDLLA polymer coating. The tensile testing procedure is based on fixation of the foam into aluminium pots by a suitable adhesive. Tensile test samples having cross-section of 10×10 mm2 and a length of 30 mm were used for the experiments. Basic fractographic analysis was applied to get relevant information about specimens' behaviour during tensile loading. In Bioglass® based scaffolds, the presence of PDLLA coating led to a significant increase of the fracture strength, which is attributed to the interaction of the polymer phase with propagating cracks, e.g. enabling a crack bridging mechanism to take place. © 2013 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.respon
Keywords: 45S5 Bioglass®; Foams; Open porosity; Scaffolds; Tensile strength